Expression of Helicobacter pylori CagA in Solanum melongena L-A Cost Effective Strategy for Vaccine Development - Mehran, Mohammad Javad; Barzigar, Rambod; Kumar, Basaralu Yadurappa Sathish; Haraprasad, Nanjundappa; Fakrudin, Bashasab; Paul, Sayan; Malla, Sudhakar; Bolideei, Mansoor (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Helicobacter pylori is implicated in several severe gastrointestinal disorders, including gastric cancer, affecting a significant global population. This study aims to exploit plant biotechnology for vaccine development by engineering brinjal (Solanum melongena L.) to express H. pylori’s cytotoxin-associated gene A (cagA) antigen. Utilizing transgenic plants as an innovative strategy not only mitigates the high costs associated with traditional vaccine production but also leverages their capacity to induce a mucosal immune response. Materials and Methods We used the brinjal variety ‘Arka Keshav’ for transformation. The cagA gene from H. pylori strain 26695 was cloned into the pBI121 vector and transferred into brinjal using Agrobacterium tumefaciens-mediated transformation. Transgenic expression was verified through PCR, quantitative real-time PCR (qPCR), Western blotting and ELISA. Immunohistochemistry was used to assess the localization of the cagA protein within the plant tissues. Results Cloning and amplification confirmed the insertion of the cagA gene approximately ~1700 bp in size. Transgenic brinjal lines were successfully generated, with distinct expression levels of cagA observed. ELISA and Western blot analyses indicated significant cagA protein expression, particularly in lines B11 and B17, which showed the highest antigen concentrations. The consistency of mRNA and protein expression validated the effectiveness of the transgenic approach. Conclusion The study demonstrates the feasibility of using genetically modified brinjal as a platform for producing edible vaccines against H. pylori. This approach not only presents a cost-effective alternative to traditional vaccines but also offers potential for enhancing accessibility in regions burdened by gastric diseases associated with H. pylori. Future research should focus on optimizing expression systems and evaluating the clinical efficacy of these plant-based vaccines.
Keywords: Helicobacter pylori; Transgenic brinjal; cagA antigen; Edible vaccines